Produksi Protease Alkalis Termostabil Dari Aspergillus flavus DUCC- K225 Dengan Ammonium Sulfat Sebagai Sumber Nitrogen - Putra, Mohammad Affan Dwica; Rukmi, MG Isworo; Pujiyanto, Sri; Mulyani, Nies S (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Protease is a protein hydrolytic enzyme which can be generated by a variety of microorganisms, including mold. Aspergillus flavus K225, DUCC is indigenous mold isolated from lime soil of Madura which is have potential as a alkaline protease producer. This research aims was to know the effect of ammonium sulfate as nitrogen source for the production of protease enzymes by Aspergillus flavus DUCC-K225. The production of alkaline protease were conducted in submerged culture medium with agitation. Fermentation medium used was modification Czapeks Dox Broth containing 2% casein. Incubation is carried out for 7 days. The results showed that ammonium sulfate is a good source of nitrogen for growth and production of aklaine protease enzyme, which is demonstrated by higher dry weight, the protease activity, the protein content and the specific activities, comparing those on standard medium using sodium nitrate as N source.